Turbulent energy dissipation rates observed by Doppler MST Radar and by rocket-borne instruments during the MIDAS/MaCWAVE campaign 2002 - Engler, N.; Latteck, R.; Strelnikov, B.; Singer, W.; Rapp, M. (Annales Geophysicae, 2005)
During the MIDAS/MaCWAVE campaign in summer 2002 we have observed turbulence using Doppler beam steering measurements obtained from the ALWIN VHF radar at Andøya/Northern Norway. This radar was operated in the Doppler beam steering mode for turbulence investigations during the campaign, as well as in spaced antenna mode, for continuously measuring the background wind field. The real-time data analysis of the Doppler radar backscattering provided the launch conditions for the sounding rockets. The spectral width data observed during the occurrence of PMSE were corrected for beam and shear broadening caused by the background wind field to obtain the turbulent part of the spectral width. The turbulent energy dissipation rates determined from the turbulent spectral width vary between 5 and 100mW kg-1 in the altitude range of 80-92km and increase with altitude. These estimations agree well with the in-situ measurements using the CONE sensor which was launched on 3 sounding rockets during the campaign.